Analysis of reporting of family violence reporting in print media in regional Western Australia. (18th April 2022) - Ringin, Luke; Moran, Monica; Thompson, Sandra C.
Abstract: Objectives : This research aimed to gain insights into the reporting of family violence (FV) and to explore any changes in FV reporting associated with a FV primary prevention initiative in Geraldton, Western Australia. Methods : An in‐depth analysis of articles published by the Geraldton Guardian in 2019 examined the nature of FV reporting. Analysis was based on deductive coding from existing literature and inductive identification of new themes. A comparative analysis examined articles from the Geraldton Guardian and Albany Advertiser over the same three‐month period in 2015, 2017 and 2019 to analyse trends in FV reporting. Results : Of 135 articles analysed, there was alignment with five previously reported themes and two new themes were identified: FV as a public health issue; and community responses to reduce FV. Episodic framing was overwhelmingly associated with court reporting. There was more reporting of efforts at primary prevention of FV over time in both newspapers. Conclusions : Local media can contribute to the promotion of community and public health issues related to FV. Efforts are needed to improve court reporting to situate FV in a broader context. Implications for public health : Concerted efforts to educate the public and journalists can support FV being recognised as a public health issue.